Effectiveness of the three-day course of natamycin for acute episodes of uncomplicated vaginal candidiasis - Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Vulvovaginal candidiasis (VVC) constitutes one of the most frequent diseases requiring gynaecological intervention. An optimal treatment for VVC which would combine high clinical and mycological efficacy with convenience for the patient is still being sought. Natamycin is a broad spectrum antifungal polyene antibiotic which has been used in gynaecology for many years. The well-proven efficacy of the 6-day course of natamycin for VVC led us to analyze the results of 3-day therapy with this antibiotic. The available literature does not contain papers evaluating clinical efficacy of the three-day course of natamycin for VVC. Objective: The aim of this study was to evaluate the clinical efficacy of the 3-day course of natamycin for acute episodes of uncomplicated VVC. Material and methods: The studied population consisted of 52 non-pregnant women with acute uncomplicated VVC diagnosed by means of subjective and objective symptoms as well as microscopic examination of the KOH preparation for the presence of fungal hyphae. The treatment efficacy was evaluated using both symptomatological and mycological criteria at two time-points (7 and 30 days after the therapy initiation). Results: At 7 days the percentages of patients in whom complete disappearance or a significant improvement in subjective and objective symptoms took place, and in whom eradication of fungi from the vagina was confirmed, were 86.5, 84.6 and 80.8%, respectively. These figures did not significantly change after the following 3 weeks of follow-up. Patient’s age, parity and the number of VVC episodes in the last 12 months did not significantly influence the efficacy of 3-day natamycin treatment. Conclusion: Short-term natamycin treatment for VVC (100 mg intravaginally once daily for 3 days) is highly efficient in both eliminating the symptoms and eradicating fungi from the vaginal ecosystem.